Sosialisasi Pemanfaatan Sampah Daur Ulang sebagai upaya Pengurangan Pencemaran Lingkungan Bagi Masyarakat - Abdul Rozaq Wallad; Diska Najwa Andini; Fadlan Arrasyid Bintang; Fikri Azka Tanjung; Sari Wulandari (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Environmental pollution due to waste is a serious problem in society. This study aims to describe the socialization activities of the use of recycled waste in Perintis Kemerdekaan Village as an effort to reduce environmental pollution. The method used is descriptive qualitative through observation, interviews, and direct socialization. The results show that socialization increases public understanding of the importance of sorting and managing waste with the 3R approach (Reduce, Reuse, Recyle). Examples of recycled products such as stationery holders, wall hangings, and flower vases have succeeded in attracting the interest of residents. This activity also encourages awareness that waste has economic potential if managed creatively. It is hoped that this kind of activity will continue to be developed to from a more environmentally friendly mindset and community habits.